Effect of bio-enriched paddy straw compost on reduction of chemical fertilisers in rice (Oryza sativa) – wheat (Triticum aestivum) cropping system - MAGESHWARAN, VELLAICHAMY; YADAV, ANUPRIYA; KUMAR, ADARSH; SRIVASTAVA, ALOK KUMAR (The Indian Journal of Agricultural Sciences, 2026)
Due to increasing awareness on the benefit of organic farming for sustainable ecosystem, there is an increase in area of organic cultivation and demand of organic inputs. The preparation and use of bio-enriched compost from agricultural residues cannot be avoided in organic farming practices. Therefore, an experiment was conducted for two years (2023 and 2024) at ICAR-National Bureau of Agriculturally Important Microorganisms, Mau, Uttar Pradesh to evaluate the bio-enriched compost prepared from paddy straw for yield and soil properties of rice– wheat cropping system. The replacement of 25% chemical fertilisers with 0.625 t/ha of bio-enriched compost resulted in increase in yield of rice and wheat compared to full dose of chemical fertilisers. Similarly, the soil TOC, TN and TK has been increased while pH and EC were maintained. The study recommended 25% replacement of chemical fertilisers with 0.625 t/ha of bio-enriched compost in rice–wheat cropping system of eastern Uttar Pradesh in order to reduce the dependency of chemical fertilisers, maintain the soil fertility, save the production cost, enhanced productivity and quality of the produce and overcome the problem of crop residue burning. In future, the combination of different organic inputs can be studied to further reduce the chemical fertilisers usage in rice–wheat cropping system.